The Interrelationship Of Some Kinematical Variables Between Launch and Landing On the Uneven Bars In Qatar World Cup Championship 2016 - Najah, Yasser (Journal of Physical Education, 2016)
The importance of the research lies in identifying the interrelationship between some kinematical variables between launch landing phases that are considered the most important phases on the uneven bars. The problem of the research lies in the great differences in landing variables among gymnasts like the height of flight and landing distance that affect the performance score. The aims of the research was to identify the vales of some kinematical variables of landing and launching phases on the uneven bars as well as identifying the interrelationships of these variables between launch and landing phases. The main experiment was conducted on 25/3/2016 in Qatar world cup championship 2016. The researchers used two cameras (120pix/sec). The data was collected and treated using proper statistical methods. The researchers concluded that there is a significant relationship between launch phase and landing phase variables in torque and launch angles and speed that play an important role in the amount of height and time of flight and landing distance that consequently affect the performance score.